Pesan Dakwah dalam Lirik Lagu Ebiet G. Ade - Syifa Hayati Islami (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2016)
Abid Ghoffar bin Aboe Dja'far or more familiarly called Ebiet G. Ade is a phenomenon of the many singers who embed the divine messages in the song. Ebiet tries to invite the listener to feel and see that God is very close and watching his servant. In the lyrics of this song can be taken a lesson about the core of Islamic teachings that should be known and amalkan by the Muslims that is Tawheed. Many Muslims are only limited to knowing about Tawheed, but not much more in understanding and practicing Him. This study uses a qualitative approach that is a documentary discourse that aims to explain the meaning of ketauhidan contained in the lyrics of the song Ebiet G. Ade. The lyrics of the song are